Cross-Cultural Pragmatic Aspects of Media Language in English and Uzbek Contexts - Bekberganov Avazbek; Bekberganova Khilola (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
The article explores cross-cultural pragmatic issues of media language in English and Uzbek contexts. The current research deals with how journalists make use of language to express meaning, politeness, and cultural values in headlines and reports. Media discourse embraces cultural identity and influences the way news is framed and interpreted. Using examples from BBC, CNN, Kun.uz, and Daryo.uz, this study follows a qualitative contrastive discourse analysis to expose differences in pragmatics in English and Uzbek media. The findings of the study revealed that English media tends towards more direct and explicit strategies of communication; meanwhile, the Uzbek media shows indirectness, politeness, and some collectivist expressions. Such differences are explained through the high-context and low-context dimensions of cultures proposed by Hall (1976). This study enriches intercultural pragmatics and translation studies with instances showing how cultural norms affect journalistic communication.